STRATEGI PROMOSI PERPUSTAKAAN KELILING KE TEMPAT IBADAH DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN TABANAN - Putri wardiani, Ni Made; Ginting, Richard Togaranta; Kawitri Resen, Putu Titah (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2021)
The study this aims for know library promotion strategy through promotion library around to place worship at Dinas Library and Archives Regency Tabanan. Library promotion is one of the efforts used by the library to introduce the library to the community by carrying out several activities related to promotion in the library. Study the using methods research. qualitative Techniques icollection iof data that at use was interview, iobservation iand documentation.The study was conducted in February 2021. In do technical analysis iof data iwriter iusing istage ipresentation ithe data iand iwithdrawal Iconclude. The library promotion strategy at the Tabanan Regency Library and Archives Service uses mobile library promotion media which can be divided into several parts, one of which is a mobile library to places of worship. Promotion of mobile libraries to places of worship has good facilities and book collections by having 1 mobile library car.   Keyword: Promotion, library   promotional Strategy, Dinas Perpusatakaan dan Kearsipan Kabupaten Tabanan